CT imaging and clinical course of asymptomatic cases with COVID-19 pneumonia at admission in Wuhan, China. Issue 1 (July 2020) - Meng, Heng; Xiong, Rui; He, Ruyuan; Lin, Weichen; Hao, Bo; Zhang, Lin; Lu, Zilong; Shen, Xiaokang; Fan, Tao; Jiang, Wenyang; Yang, Wenbin; Li, Tao; et al.
Summary: Purpose: Aimed to characterize the CT imaging and clinical course of asymptomatic cases with COVID-19 pneumonia. Methods: Asymptomatic cases with COVID-19 pneumonia confirmed by SARS-COV-2 nucleic acid testing in Renmin Hospital of Wuhan University were retrospectively enrolled. The characteristics of CT imaging and clinical feature were collected and analyzed. Results: 58 asymptomatic cases with COVID-19 pneumonia admitted to our hospital between Jan 1, 2020 and Feb 23, 2020 were enrolled. All patients had history of exposure to SARS-CoV-2. On admission, patients had no symptoms and laboratory findings were normal. The predominant feature of CT findings in this cohort was ground glass opacity (GGO) (55, 94.8%) with peripheral (44, 75.9%) distribution, unilateral location (34, 58.6%) and mostly involving one or two lobes (38, 65.5%), often accompanied by characteristic signs. After short-term follow-up, 16 patients (27.6%) presented symptoms with lower lymphocyte count and higher CRP, mainly including fever, cough and fatigue. The evolution of lesions on CT imaging were observed in 10 patients (17.2%). The average days of hospitalization was19.80±10.82 days, and was significantly longer in progression patients (28.60±7.55 day). Conclusion: CT imaging of asymptomatic cases with COVID-19 pneumonia has definite characteristics. Since asymptomatic infections as "covert transmitter", and some patients can progress rapidly in the short term. It is essential to pay attention to the surveillance of asymptomatic patients with COVID-19. CT scan has great value in screening and detecting patients with COVID-19 pneumonia, especially in the highly suspicious, asymptomatic cases with negative nucleic acid testing.